Vaccination in England: a review of why business as usual is not enough to maintain coverage - Tim Crocker-Buque; Sandra Mounier-Jack (BMC, 2018)
Abstract Background The vaccine system in England underwent radical changes in 2013 following the implementation of the Health and Social Care Act. There have since been multi-year decreases in coverage of many vaccines. Healthcare professionals have reported finding the new system fragmented and challenging. This study aims to produce a logic model of the new system and evaluate the available evidence for interventions to improve coverage. Methods We undertook qualitative document analysis to develop the logic model using process evaluation methods. We performed a systematic review by searching 12 databases with a broad search strategy to identify interventions studied in England conducted between 2006 and 2016 and evaluated their effectiveness. We then compared the evidence base to the logic model. Results We analysed 83 documents and developed a logic model describing the core inputs, processes, activities, outputs, outcomes and impacts of the new vaccination system alongside the programmatic assumptions for each stage. Of 9,615 unique articles, we screened 624 abstracts, 45 full-text articles, and included 16 studies: 8 randomised controlled trials and 8 quasi-experimental studies. Four studies suggest that modifications to the contracting and incentive systems can increase coverage, but changes to other programme inputs (e.g. human or capital resources) were not evaluated. Four multi-component intervention studies modified activities and outputs from within a GP practice to increase coverage, but were part of campaigns or projects. Thus, many potentially modifiable factors relating to routine programme implementation remain unexplored. Reminder/recall systems are under-studied in England; incentive payments to adolescents may be effective; and only two studies evaluated carer information. Conclusions The evidence base for interventions to increase immunisation coverage in the new system in England are limited by a small number of studies and by significant risk of bias. Several areas important to primary care remain unexplored as targets for interventions, especially modification to organisational management.